The use of dihydroxy fatty acid and palm-based polyol as selected components of envo-diesel fuel blends to reduce c.i. engine gaseous emissions and carbon deposits - Husnawan, H.; Masjuki, Haji Hassan; Mahlia, T.M.I.; Saifullah, M.G.; Kalam, M.A. (2009)
Nowadays, engine problems such as higher NOx, increase in smoke content and low brake power output due to biofuel fueled engine have been reduced by several improvements by using additives or modifications on engine itself. This paper presents a type of compositions and proper combination of selected chemical components which may be used in palm oleindiesel blends namely “Envo-Diesel”. The blended component was designed as an additive package which was blended with diesel-biofuel at 99:1 up to 95:5 percent ratios. Blended fuels with additive have been used in the single cylinder engine which operated under 2000 rpm for 100 hours. Engine performance and emissions tests were conducted as well as engine deposit analysis was done after 100 hours engine operation time. The result was found that by using combined additive engine fuel consumption was decreased about 5%, NOx and SOx emission also reduced about 10% and carbon deposit was found less compared to other fuels especially for higher percentage of additive. Other results such as engine power and CO emission were found quite similar with 100% diesel fuel. These phenomena was shown that by using selected additive in certain amount found to be suitable to reduce diesel engine consumption and exhaust emissions as well as minimizing carbon deposit.